Importance of collection tube during clinical studies of oseltamivir. - Lindegardh, N; Davies, G; Hien, T; Farrar, J; Singhasivanon, P; Day, N; White, N (2007)
Ex vivo conversion of the anti-influenza drug oseltamivir to its active metabolite can be inhibited by the esterase inhibitor dichlorvos or by using commercial fluoride-oxalate tubes. Oseltamivir and its active metabolite remain intact in plasma samples during a proposed virus heat inactivation step: incubation at 60 degrees C for 45 min.